El teísmo metodológicamente ficcional de Immanuel Kant - Moya Bedoya, Juan Diego (2005)
This monographical contribution examines Kant’s methodologically fictional theism, i. e., a reflexive thesis according to which the transcendental ideal (prototypon transcendentale), theoretically conceived, amounts to nothing more than a heuristical device of reason. The function of this device is to guarantee the architectonical cognitive integrity of human empirical knowledge, h. e., the only possible human knowledge on sensible objects.